Relevance of hematological parameters in patients with recurrent aphthous stomatitis - Alberto Rodriguez-Archilla; Maria Brykova (Wolters Kluwer Medknow Publications, 2019)
Background: Recurrent aphthous stomatitis (RAS) continues to be a very common ulcerative disease of the oral mucosa, affecting approximately 20% of the general population. Hematinic deficiencies have been considered as a possible triggering factor, being iron, Vitamin B12, or folic acid deficiencies two times more frequent in patients with RAS. Objective: The objective was to assess the hematological parameters as possible etiological factors of RAS. Materials and Methods: A PubMed search of articles on hematological parameters in RAS was conducted. From 93 articles published between 1954 and 2018 (64 with full-text availability), 45 were excluded for several reasons: studies without a control group (17), studies with no clinical data (12), and studies with nonusable data (16). Data were processed using the statistical software RevMan 5.3 (The Cochrane Collaboration, Oxford, UK). For continuous outcomes, the estimates of effects of an intervention were expressed as mean differences using the inverse variance method, and for dichotomous outcomes, the estimates of effects of an intervention were expressed as odds ratio (OR) using Mantel-Haenszel method, both with 95% confidence intervals. Results: Nineteen studies of hematological parameters on RAS were included in this meta-analysis. RAS patients had a significantly higher risk of presenting low levels, together with lower concentrations, of hemoglobin (OR: 17.30), iron (OR: 6.67), folic acid (OR: 4.98), Vitamin B12(OR: 3.99), ferritin (OR: 2.86), and higher levels of homocysteine (OR: 7.22). Conclusion: Hematological disturbances may be an etiological factor of RAS.